From photography to walls: the role of photojournalism and political art in the construction of the figures of Darío Santillán and Maximiliano Kosteki (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article deals with the way in which photojournalism and political art contributed to the construction of an iconography of Darío Santillán and Maximiliano Kosteki, piqueteros activist killed by the police on June 26, 2002 in the Avellaneda station. The photographs of that repression were crucial to the reconstruction of the events that ended with the murders of both activists. We refer to the images where we see Santillán assisting his fellow Kosteki, with an outstretched arm, an instant before being killed. This gesture captured by the camera was retaken as a symbol of piquetero solidarity, replicated in stencils, murals and flags. We propose a series of reflections on the evolution of those images from the notions of Pathosformel, Nachlebenand image-act, to think about the relationship between body, image and memory.
Keywords: Political Iconography; Photojournalism; Memory.